Wafer Level Packaging Technology Applied to Pixel Detectors - Conci, Paolo; Darbo, Giovanni; Gaudiello, Andrea; Gemme, Claudia; Girardi, Stefano; Lapertosa, Alessandro; Mattedi, Francesca; Volpe, Alessio (Frontiers in Physics, 2021)
Pixel technology is commonly used in the tracking systems of High Energy Physics detectors with physical areas that have largely increased in the last decades. To ease the production of several square meters of sensitive area, the possibility of using the industrial Wafer Level Packaging to reassemble good single sensor tiles from multiple wafers into a reconstructed full wafer is investigated. This process reconstructs wafers by compression molding using silicon charged epoxy resin. We tested high glass transition temperature low-stress epoxy resins filled with silica particles to best match the thermal expansion of the silicon dies. These resins are developed and characterized for industrial processes, designed specifically for the fan-out wafer-level package and panel-level packaging. In order to be compatible with wafer processing during the hybridization of the pixel detectors, such as the bump-bonding, the reconstructed wafer must respect challenging technical requirements. Wafer planarity, tile positioning accuracy, and overall thickness are amongst the main ones. In this paper the description of the process is given and preliminary results on a few reconstructed wafers using dummy tiles are reported. Strategies for Wafer Level Packaging improvements are discussed together with future applications to 3D sensors or CMOS pixel detectors.